Unmasking Methicillin-resistant Staphylococcus argenteus: pathogenic potential, diagnostic pitfalls and antibiotic resistance of MRSArg in Norway 2008–2019 - Rønning, Torunn Gresdal; Enger, Hege; Zaragkoulias, Kyriakos; Ås, Christina Gabrielsen (Frontiers in Microbiology, 2026)
BackgroundStaphylococcus argenteus is a coagulase-positive species within the Staphylococcus aureus complex that may carry the mecA gene, conferring methicillin resistance. Despite its clinical relevance, methicillin-resistant S. argenteus (MRSArg) remains underreported and poorly characterized in many regions.AimThis study presents the first nationwide analysis of MRSArg in Norway, detected among MRSA 18,152 isolates submitted to the Norwegian MRSA Reference Laboratory between 2008 and 2019.MethodsClinical and epidemiological data were retrieved from national surveillance systems and laboratory records, enabling classification into healthcare- and community-associated categories. A representative panel of MRSArg genotypes (n = 25) was inoculated onto four MRSA-selective chromogenic agars for qualitative assessment of growth characteristics and colony pigmentation, and into two enrichment broths for quantitative evaluation of stationary-phase cell density. Identification was performed using MALDI-ToF MS and GeneXpert assays. Whole genome sequencing of 160 isolates enabled phylogenetic analysis, resistance and virulence profiling, and cgMLST. A species-specific multiplex PCR targeting yhfT, mecA, and lukE, along with adapted spa-typing primers, was developed for accurate molecular identification and typing.ResultsA total of 160 mecA-positive MRSArg strains (0.9%) were identified, corresponding to 142 unique patients. Most cases were community-associated and linked to international acquisition, particularly from Southeast Asia. However, 36% were healthcare-associated, including a notable proportion among healthcare workers. The dominant genotype was spa-type t6675/ST2250 (50%), with increasing diversity observed after 2014. A species-specific multiplex-PCR and sanger sequencing primers for detection and genotyping of MRSArg were developed and validated.ConclusionMRSArg is an emerging pathogen in Norway with both community and healthcare relevance. Improved molecular diagnostics are essential for accurate detection and surveillance.